Non-commutative complex differential geometry - Edwin Beggs (Journal of Geometry and Physics, 2013)
The paper sets out the theory of noncommutative complex differential structures, and relates it to the existing literature on noncommutative algebraic geometry. The eventual idea is to to motivate work to make a noncommutative analogue of Serre's Geometric / Algebraic correspondence.